Effectiveness of educational intervention on knowledge regarding oral hygiene among basic level students, Pharping Nepal. - Balami, Rashila (2021)
ABSTRACT: Oral health a pivotal role in the overall health and wellbeing. Dental caries and periodontal diseases are the two foremost oral pathologies that remain widely prevalent and affect all populations throughout the lifespan. Knowledge of oral hygiene can help to prevent and reduce the burden of oral disease and promote oral health. Schools can be an important setting for health education programmes, controlling the growing burden of oral disease and promoting oral health. The purpose of this study was to assess the effectiveness of educational intervention on knowledge regarding oral hygiene among basic level students of Shikharapur community school, Pharphing Kathmandu. A pre-experimental one group pretest posttest design was used. Census method was used for determining the sample of the study, which was 102. Data was collected by using structured questionnaire which consists of questions related to socio-demographic information and questions related to knowledge regarding oral hygiene. All the collected data were analyzed by using SPSS version 20 and interpreted in the form of frequency, mean, percentage, standard deviation. Pre-test and Post-test mean scores were compared by using inferential statistics i.e, paired test. This study revealed that majority (40.2%) of the respondents were of age 13 years with mean age 12.95, SD+- 1.075. Similarly more than half (55.9%) of the respondents were female. Furthermore, this study finding showed that pre-test knowledge mean score was 13.33 and post-test knowledge mean score was 27.98 with t-test value 29.45. The different in knowledge between pre and post-test was found to be highly significant (p=0.000). Study findings revealed that there is positive change in knowledge after educational intervention. Therefore, educational package on oral hygiene can be launched in various settings to increase the knowledge of school children. Keywords: Basic level students, Educational intervention, Knowledge regarding oral hygiene.